Determination of hydroquinone in a square wave voltammetry procedure using a graphite-polyurethane composite electrode - Cervini, Priscila; Cavalheiro, Éder Tadeu Gomes (Eclética Química, 2006)
In order to a better characterization of a graphite-polyurethane composite intended to be used as a voltammetric sensor, the performance in a square wave voltammetric procedure was investigated. Using hydroquinone (HQ) as a probe, the electrode showed to be useful in square wave voltammetry with limit of detection of 0.28 µmol L-1, with recoveries between 99.1 and 101.5%. The results of the proposed method agreed with HPLC ones within 95% confidence level.